Sistem Monitoring Temperatur Suhu Menggunakan Metode Message Queue Telemetry Transport (MQTT) - Jaya, Gede Suwasnata; Suputra, I Putu Gede Hendra; Mogi, I Komang Ari; Cahyadi Putra, I Gusti Ngurah Anom; Astuti, Luh Gde; Sanjaya, Ngurah Agus (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 4 (2023): JELIKU Volume 11 No 4, May 2023, 2022)
This research implements the NodeMCU ESP8266 moduleeto display the number of temperatures. NodeMCU ESP8266 will function as a data sender that will send temperature optimalization which will later be displayed on the hardware when running the prepared program. From the test results on the implementation of the WiFi NodeMCU ESP8266 module for these temperatures, it has been running well where the NodeMCU ESP8266 can send data in the form of numbers from the temperature. There are several protocols that have developed for the implementationnof the Internet of things, including Message Queue TelemetryyTransport (MQTT). Based on the test results, the system can connect to local MQTT servers and global MQTT servers, capable of sending data (publish) and receiving data (subscribe).